PENERAPAN MODEL PEMBELAJARAN WORD SQUARE UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA PADA MATERI IKLAN KELAS V UPT SD NEGERI 237 PINRANG - Ilmi, Nur; Halik, Abdul; St.Hajar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This Classroom Action Research (PTK) focuses on the active learning of class V students at UPT SD Negeri 237 Pinrang. This research is qualitative research with data collection techniques used, namely observation and documentation. The subjects of this research were 24 students and 1 teacher. The research was carried out in two cycles. In the first cycle, learning activities reached Low qualifications and the learning process in teacher activities reached Fair qualifications (C), while in student activities reached Fair qualifications (C). while in cycle II learning activities were at High qualifications and teacher activities achieved Good qualifications (B), while student activities achieved Good qualifications (B). The conclusion of this research is that the application of the word square learning model can improve the learning process and active learning of students in Indonesian for class V UPT SD Negeri 237 Pinrang students.